Analisis Kepuasan Peternak Sapi Pedaging terhadap Kinerja Petugas Inseminasi Buatan (IB) di Kabupaten Lombok Tengah - Saparudin Saparudin; Soekardono Soekardono; Enny Yuliani (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study analyzes the level of satisfaction of broiler farmers with the performance of Artificial Insemination (IB) officers in Central Lombok Regency. A quantitative survey method with a descriptive approach was used to collect data from 99 farmers spread across four sub-districts. Service per Conception (S/C), Conception Rate (CR), and Non Return Rate (NRR) parameters were used to assess the technical performance of IB officers. The results of the study show that the level of satisfaction varies between sub-districts, with the performance of IB officers in Jonggat and Pringgarata Districts being more optimal than other regions. This analysis provides recommendations in the form of increasing the technical capacity of officers, as well as increasing education for farmers to support the success of IB programs in the region.